Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Motivasi Kerja (Indo-MathEdu Intellectuals Journal, 2024)
Work motivation is an important factor in improving employee performance and achieving organizational goals. Human Resource Management (HRM) plays a crucial role in motivating employees through various strategies and policies. The method used in this study is a type of qualitative research. The data sources obtained in this study are from the results of library research from various sources. The main source of data for this research is the results of research published on google scholar. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of this study are obtained how the role of human resource management in increasing work motivation, effective human resource management strategies and policies to increase work motivation, as well as challenges and solutions in the implementation of human resource management to increase work motivation